Contextualization and Synergy of the Concept of Justice in Islamic Economic Development - Ahmad Mahfudzi Mafrudlo; Nurrohman Nurrohman (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2022)
The complexity of socio-economic problems has become a serious global problem. Moreover, Islamic economic development requires attention and seriousness in order to balance all needs and minimize all complexities. With a balance that leads to the concept of justice in an Islamic perspective, implementation becomes a necessity. The concept of justice will provide a clear path for the implementation of the Islamic economic system. By using descriptive analysis writing method and with primary and secondary reference sources. This research is included in the category of library research or research activities related to literature. As the embodiment of Islamic economic values, contextualization and synergy of the concept of justice must be pursued as much as possible. Seeing the current discourse in the economic realm, justice has entered global policy. So that Islamic economic development that has contributed to economic development can be implemented comprehensively.